Efektivitas dan Efisiensi Pengelolaan Keuangan Daerah di Kota Makassar - Budiandriani; Sri Wahyuni Al Aqzah; Sitti Rahmi Razak; Mahfud Nurnajamuddin (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
This research aims to determine and analyze the effectiveness and efficiency of regional financial management in Makasar City. The data used is secondary data in the form of financial reports from the Makassar City Regional Financial and Asset Management Agency. This research uses a quantitative approach, namely by analyzing the effectiveness and efficiency of regional financial management and describing research findings. The research results found that regional financial management in Makassar City in 2017-2022 was in the effective category, namely with an average of 92.21% per year. Meanwhile, based on the level of efficiency, it shows that in 2017-2022 the regional financial management of Makassar City was in the less efficient category with an average of 96.80% per year.